Please Don't Tap The Glass - Baker, Mackenzie Anne (Tufts Archival Research Center, 2019)
Background: Why do I love what I fear? There are things that keep me awake at night, wondering if they will be my downfall. These things fascinate me. They also give me anxiety. In my work, past and present, I have always touched on how anxiety can affect people, how it drives us to feel lost within ourselves. But I always felt like there was something more to it than just that. Working through this thought after feeling stuck in my work and creation process it became apparent that while I was focusing clearly on anxiety itself, I was ignoring everything that triggered it. Anxiety has more depth to it than just being anxiety and at times there is a mysticism to it that makes it all the more complex.; Keywords: anxiety, depression, marine life, water, thalassaphobia, claustrophobia, pediophobia, sleep paralysis, ink, pen, paper, organic life, aquarium, fears, irrational, rational, unknown, haunting, faded, stress relief, therapy, therapeutic, paper, sculpture, ocean, water